The First Bulgarian Exarch Anfim I Activities at the Final Stage of the Bulgarian National Liberation Movement in the 1870s - V. V. Bondareva (Научный диалог)
The historical significance, character, content, target orientation and principles of exarch Anfim I (the first head of the Bulgarian Orthodox Church) activities at the final stage of the Bulgarian national liberation movement in the 1870s are analyzed. Characteristics of the charismatic qualities of the exarch Anfim I as a national spiritual leader, a deep patriot and a true fighter for the Bulgarian national idea, repeatedly risking his life are presented. The main attention is paid to his activity in organizing and strengthening the independent national-church organization of the Bulgarians as a key structure that ensured national identification and prototype of the Bulgarian statehood under Ottoman rule. Greco-Bulgarian contradictions are considered as the most important aspect of the struggle to ensure the national qualities of the independent Bulgarian church, headed by the Exarch Anfim I. The social political views of the exarch Anfim I, characterized by pronounced Russophilia, are presented as strict principles that organized his activities. In conditions of increasing oppression by the Turks, the Bulgarian exarch Anfim I is shown as their ardent and active defender in front of the Ottoman government, seeking help from Russia and the states of Europe. It is concluded that the activities of the Exarch Anfim I had an exceptionally important, strategic character during the national liberation movement of the Bulgarians and was aimed at providing the Bulgarian national idea, historically deeply interconnected with Orthodoxy and the Slavs.